2013
DOI: 10.1136/bmjopen-2013-002726
|View full text |Cite
|
Sign up to set email alerts
|

A randomised controlled trial to improve the role of the general practitioner in cancer rehabilitation: effect on patients’ satisfaction with their general practitioners

Abstract: ObjectiveTo test whether a complex intervention facilitating early cancer rehabilitation by involvement of the general practitioner (GP) soon after diagnosis improves patients’ satisfaction with their GPs.DesignA cluster randomised controlled trial. All general practices in Denmark were randomised to an intervention or a control group before the start of the study. Patients included those with cancer who were subsequently allocated to either group based on the randomisation status of their GP.ParticipantsAdult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 28 publications
(26 reference statements)
0
16
1
Order By: Relevance
“…Innovative, shared follow‐up schemes allow a two‐way exchange of information and create ties between GPs and specialist centres . These initiatives may foster greater patient trust; however, in a recent controlled trial of an attempt to increase the involvement of GPs in cancer rehabilitation, this aim was not achieved . Further studies must determine how GPs can be involved in the management of cancer treatment and post‐treatment care.…”
Section: Discussionmentioning
confidence: 99%
“…Innovative, shared follow‐up schemes allow a two‐way exchange of information and create ties between GPs and specialist centres . These initiatives may foster greater patient trust; however, in a recent controlled trial of an attempt to increase the involvement of GPs in cancer rehabilitation, this aim was not achieved . Further studies must determine how GPs can be involved in the management of cancer treatment and post‐treatment care.…”
Section: Discussionmentioning
confidence: 99%
“…Five systematic reviews, 17–21 six RCTs 22–27 and 11 non-randomised studies 28–38 comprised the review. The six RCTs and 11 non-randomised studies were not already included in the five systematic reviews.…”
Section: Resultsmentioning
confidence: 99%
“…Six RCTs were included in the review, one each from Canada, 23 Australia, 24 the UK 25 and the USA, 26 and two from Denmark. 22 27 Studies were designed for all cancers, 22 haematological, breast, ovarian and colorectal cancers, 24 breast, colorectal and lung cancers, 25 26 breast cancer only 23 and colorectal cancer only. 27 Two RCTs examined interventions that targeted transition from diagnosis through to treatment, 26 27 one study targeted only treatment, 24 two studies targeted transition from treatment through to survivorship 22 25 and one study targeted survivorship specifically.…”
Section: Resultsmentioning
confidence: 99%
“…As a recent Danish study demonstrated, an intervention encouraging the early involvement of GPs does not suffice to improve patients' satisfaction with their GPs. [7] This study potentially provides GPs with the key to understanding cancer patients' behaviours and attitudes. During the initial cancer treatment phase, GPs were found to play a special role in the physicianpatient relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies of GPs are based on data gathered either from GPs themselves using qualitative research techniques [2][3][4] or from patients via quantitative techniques. [5][6][7][8][9] Six qualitative studies in which patients were interviewed, stressed the importance of GPs in the early follow-up phase, particularly for emotional support and medical management. [10][11][12][13][14][15] To a very significant extent, these issues are specific to the healthcare system in the country in which they occur.…”
Section: Introductionmentioning
confidence: 99%